2007
DOI: 10.1063/1.2719650
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of forward voltage drift in 4H-SiC p-i-n diodes via low temperature annealing

Abstract: Recent reports have shown that Shockley stacking fault (SSF) growth in 4H-SiC may be reversed via low temperature (210–600°C) annealing. It is not clear if the associated drift in the forward voltage drop (Vf) is also reversed. Here we show that annealing of SSFs causes the complete and repeatable recovery of Vf. Furthermore, by looking at the time-dependent recovery of Vf during both the current stressing and thermal annealing of a single diode, we ascertain that the mechanisms for these two processes are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 12 publications
4
54
0
Order By: Relevance
“…First of all, as reported previously by Caldwell et al 13,14 and Miyanagi et al 15 it should be reiterated that not only can SSFs expand, but due to low-temperature (400°C to 700°C) annealing, the SSFs have been shown to contract, which is associated with a complete and repeatable recovery of the V f drift as well. 14 Here, the time constants for this recovery as a function of temperature were reported and an activation energy of 1.3 ± 0.3 eV was determined.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…First of all, as reported previously by Caldwell et al 13,14 and Miyanagi et al 15 it should be reiterated that not only can SSFs expand, but due to low-temperature (400°C to 700°C) annealing, the SSFs have been shown to contract, which is associated with a complete and repeatable recovery of the V f drift as well. 14 Here, the time constants for this recovery as a function of temperature were reported and an activation energy of 1.3 ± 0.3 eV was determined.…”
Section: Discussionmentioning
confidence: 73%
“…[13][14][15]19 However, direct comparisons between the activation energy we report for the annealing process with those currently discussed in the literature 16,17 are not straightforward. Previous measurements involved determining the distance a given partial dislocation propagated due to mechanical stress, in the absence of injected electron-hole pairs (EHPs) 16 or due to the optical injection of EHPs via above band gap light, 17 which provided activation energies of 2.5 and 0.25 eV, respectively.…”
Section: Annealing Of Ssfs/recovery Of V F Driftmentioning
confidence: 90%
See 2 more Smart Citations
“…However, such defects may also act as nanometer-scale sources of modified SPhP response that can be useful in the design of patterned nanophotonic or metamaterial devices. For instance, the incorporation of stacking faults in silicon carbide [69,70,[163][164][165][166][167][168][169][170][171][172][173] could provide a means to modify the Reststrahlen band and, therefore, the SPhP response of specific nanostructures or nanophotonic/metamaterial designs. Experimental evidence for this were reported by Ocelic et al [162] where it was demonstrated that the SPhP response could be severely damped via the patterned implantation of Be 3+ ions into a SiC surface using ion beam implantation.…”
Section: Lattice Properties and Optic Phonons: Dispersion Lifetimes mentioning
confidence: 99%